Clinically staged cT2 adenocarcinomas of the gastroesophageal junction: accuracy of staging and therapeutic consequences - Vallböhmer, Daniel; Peters, Leila; Blank, Susanne; Kraus, Sebastian; Stoecklein, Nikolas Hendrik; Knoefel, Wolfram T.; Büchler, Markus W.; Ott, Katja (Oncology research and treatment, 2014)
Background: Multimodality treatment options in locally advanced adenocarcinomas of the esophagogastric junction (AEGs) have been established in the last years. However, the therapeutic approach in patients with clinically staged cT2 tumors remains controversial. The most important determinant is the accuracy of clinical staging. We aimed to evaluate the association of clinical and histopathological staging in patients with cT2 tumors in respect of possible therapeutic consequences. Patients and Methods: Between 2001 and 2011, 71 patients with AEG tumors were clinically staged as cT2 (cN0 = 48 (68%); cN+ = 23 (32%)) and underwent surgical resection. Results: A primary tumor resection was performed in 59 (83%) patients while 12 (17%) patients received neoadjuvant therapy. Primarily resected patients showed the following pT/pN categories: pT1: 13 (22%), pT2: 35 (59%), pT3: 11 (19%), pN0: 23 (39%), whereas the clinical/histopathological pN category included 55% of the patients. Neoadjuvantly treated patients showed the following pT/pN categories: ypT0: 3 (25%), ypT1: 3 (25%), ypT2: 6 (50%), ypN0: 6 (50%). The overall survival of primarily resected patients compared with patients undergoing neoadjuvant therapy was not significantly different. Conclusions: The accuracy of clinical staging in patients with cT2 tumors of the gastroesophageal junction is poor. As in primarily resected patients, over- and understaging balance each other; correct pretherapeutic staging occurs in just about 60% of the patients. Moreover, our study suggests that a radical surgical resection with adequate lymphadenectomy seems to be appropriate for cT2N0 and even in cT2N+ tumors, since down-categorizing and prognosis are not improved for neoadjuvantly treated patients. However, the data have to be interpreted with caution because of the small patient numbers.